2012
DOI: 10.1371/journal.pone.0039329
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3 (GSK3) Inhibitor, SB-216763, Promotes Pluripotency in Mouse Embryonic Stem Cells

Abstract: Canonical Wnt/β-catenin signaling has been suggested to promote self-renewal of pluripotent mouse and human embryonic stem cells. Here, we show that SB-216763, a glycogen synthase kinase-3 (GSK3) inhibitor, can maintain mouse embryonic stem cells (mESCs) in a pluripotent state in the absence of exogenous leukemia inhibitory factor (LIF) when cultured on mouse embryonic fibroblasts (MEFs). MESCs maintained with SB-216763 for one month were morphologically indistinguishable from LIF-treated mESCs and expressed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 60 publications
(120 reference statements)
1
28
1
Order By: Relevance
“…21 It has been reported that SB216763 (ATP-competitive), a GSK3 inhibitor, effectively activated -catenin-mediated transcription. 22 Naito et al 23 showed that GSK3 nuclear expression was associated with highgrade tumors, metastasis, and worse survival in bladder cancer patients. Dose and time-dependent SB216763 improved the cytotoxic effect against the two human urothelial carcinoma cell lines, UMUC3 and UMUC14, suggesting potential therapeutic uses for GSK3 inhibitors.…”
mentioning
confidence: 99%
“…21 It has been reported that SB216763 (ATP-competitive), a GSK3 inhibitor, effectively activated -catenin-mediated transcription. 22 Naito et al 23 showed that GSK3 nuclear expression was associated with highgrade tumors, metastasis, and worse survival in bladder cancer patients. Dose and time-dependent SB216763 improved the cytotoxic effect against the two human urothelial carcinoma cell lines, UMUC3 and UMUC14, suggesting potential therapeutic uses for GSK3 inhibitors.…”
mentioning
confidence: 99%
“…However, during development, GSK-3 activity enhances neuronal differentiation of radial glia and reduces progenitor expansion (Kim et al, 2009). In agreement with these observations, GSK-3 inhibitors significantly improve the reprogramming efficiency of fibroblasts towards pluripotency (Kirby et al, 2012;Lyssiotis et al, 2009) and facilitate self-renewal of mouse embryonic stem cells (Knockaert et al, 2002), probably through activation of Wnt signalling (Marson et al, 2008). These observations suggest that the downregulation of the GSK-3 pathway opposes neuronal differentiation and promotes a progenitor-like stage.…”
Section: Direct Neuronal Reprogramming: Learning From Developmentmentioning
confidence: 63%
“…In an attempt to expand Isl1 + cells, we induced Wnt/ β -catenin, a signaling pathway known to support self-renewal of Isl1 + cardiac cells (Figure 3(a)). When SB-216763 [29], a GSK3 inhibitor, was added at days 5–8, significant expansion of Isl1 + cells was observed at d12 (Figure 3(b)). …”
Section: Resultsmentioning
confidence: 99%